A critical appraisal of the misoprostol removable, controlled-release vaginal delivery system of labor induction - Patte C; Deruelle P (Dove Medical Press, 2015)
Charlotte Patte,1 Philippe Deruelle1,21Lille University Hospital, Jeanne De Flandre Maternity, 2UPRES EA 4489, Environnement périnatal et santé, Faculté de médecine Henri Warembourg, Université Lille 2, Lille, France Background: Induction of labor is a major issue in pregnancy management. Finding strategies to increase rate and decrease time to vaginal delivery is an important goal, but maternal or neonatal safety must remain the primary objective. Misoprostol is a synthetic analogue of prostaglandin used off label to ripen the cervix and induce labor. The misoprostol vaginal insert (MVI) was designed to allow a controlled-release delivery of misoprostol (from 50 to 200 µg) with a removal tape. The objective of this review was to make a critical appraisal of this device referring to the literature.Methods: A literature search was performed in the PubMed and Cochrane databases using the keywords “vaginal misoprostol insert”.Results: Several studies compared different doses of MVI (50, 100, 150, and 200 µg) with the 10 mg dinoprostone insert. The 100 µg MVI compared with the dinoprostone vaginal insert (DVI) showed similar efficacy and no significant differences in cesarean delivery rate. MVI 200 µg compared with DVI showed a reduced time to vaginal delivery and oxytocin need but had an increased risk of uterine hyperstimulation. The rate of hyperstimulation syndrome was two to three times more frequent with the 200 µg MVI than the 100 µg.Conclusion: Current data suggest that the 100 µg MVI would provide the best balance between efficacy and safety. Further studies should be performed to evaluate this dose, especially in high-risk situations needing induction of labor. Keywords: prostaglandins, efficacy, safety, pregnancy